The interplay of gender, work and family in Portuguese families. (1st April 2012) - ,; ,; ,
Abstract : Portugal stands out in the European context of work and family relations for not fitting either into a traditional male breadwinner model or into a modern equitable model. Indeed, Portuguese society is characterised both by a high labour-market participation of both men and women and a gender-traditional division of domestic and caring work, where women do the majority of tasks. This paper reports on trends regarding the division of paid and unpaid labour over recent decades in Portugal. Challenging traditional sociological and demographic explanations, the scope of this review is to offer a psycho-social approach to the antecedents and outcomes of this division, as well as the processes individuals and families engage in to deal with multiple roles. Looking at the division of paid and unpaid labour through a gender lens, we conclude that, despite some changes in attitudes and practices, the display of gender roles still shapes both work and family relations in Portugal.